EVALUASI KETEPATAN PEMBERIAN ANTIBIOTIK PADA PASIEN ANAK-ANAK DI RAWAT JALAN RUMAH SAKIT KARANGGEDE SISMA MEDIKA BOYOLALI - Annisa Zulfa Hamida; Eko Retnowati; Istiannatus Sunnah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of antibiotics in pediatric patients requires special evaluation due to the risk of inappropriate therapy and its contribution to antibiotic resistance. Differences in pharmacokinetic characteristics in children necessitate rational and standardized antibiotic use. This study aimed to evaluate the appropriateness of antibiotic use among outpatient pediatric patients aged 0–12 years at Karanggede Sisma Medika Hospital, Boyolali, using the Gyssens method to assess the rationality of antibiotic therapy. This study employed a descriptive observational design with a retrospective approach using 190 medical records. The inclusion criteria consisted of outpatient pediatric medical records of patients receiving antibiotic therapy with complete demographic and clinical data, while patients referred to other hospitals were excluded. Data were analyzed univariately to describe the frequency distribution and percentages of patient characteristics and the appropriateness of antibiotic use. The results showed that most antibiotic use was rational (93.89%), while inappropriate use accounted for 6.11%, including incorrect dosage (0.76%), inappropriate antibiotic selection (3.05%), and antibiotic administration without indication (2.29%). These findings indicate that antibiotic use among outpatient pediatric patients was generally appropriate; however, periodic evaluation remains necessary to prevent antibiotic resistance. Keywords: Antibiotics, Pediatric Patients, Outpatient Care, Gyssens Method, Antibiotic Rationality